2012
DOI: 10.1590/s2237-93632012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of topical n-acetylcysteine in diversion colitis

Abstract: Introduction: Diversion colitis (DC) is a benign condition characterized by the appearance of inflammation in the mucosa of the colon or rectum devoid of fecal stream. Oxidative stress has been associated with the etiopathogenesis of the disease. N-acetylcysteine (NAC) is a substance with antioxidant properties, used in different treatments of inflammatory diseases. The purpose of this study was to evaluate the effects of topical applications of NAC in an experimental model of DC. Methods: Thirty-six Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…However, SCF has antioxidant activity, and the intestinal bypass significantly increases the production of ROS 9,33 . As demonstrated with other substances that possess antioxidant activity (5-ASA, n-acetylcysteine and aqueous extract of Ilex paraguariensis), it is also possible that the SCF has the same antioxidant effects on excluded sigmoid traffic mucosa, preventing epithelial assault, neutrophil infiltration and apoptosis of cells producing mucin 10,11,14 .…”
Section: (5) 2015 -335mentioning
confidence: 93%
See 3 more Smart Citations
“…However, SCF has antioxidant activity, and the intestinal bypass significantly increases the production of ROS 9,33 . As demonstrated with other substances that possess antioxidant activity (5-ASA, n-acetylcysteine and aqueous extract of Ilex paraguariensis), it is also possible that the SCF has the same antioxidant effects on excluded sigmoid traffic mucosa, preventing epithelial assault, neutrophil infiltration and apoptosis of cells producing mucin 10,11,14 .…”
Section: (5) 2015 -335mentioning
confidence: 93%
“…An experimental study showed that it is possible to trigger the onset of epithelial lesions such as those found in the DC by applying enemas with hydrogen peroxide, a potent donor of ROS 15 . The possibility that ROS may trigger the onset of DC gained more support after studies demonstrated that the application of enemas with antioxidants, such as 5-ASA and N-acetylcysteine, to the excluded colon is effective in controlling the disease 11,14,36 .…”
Section: (5) 2015 -335mentioning
confidence: 99%
See 2 more Smart Citations
“…Both substances reduced the levels of oxidative stress in the mucosa of the excluded colon, suppressed the inflammatory process, and promoted epithelial healing 17 - 20 . Despite having a remarkable antioxidant effect, due to its low ability to adhere to the colonic mucosa, NAC requires successive enema applications, which made its use impractical 18 , 19 . In contrast, SCF, in addition to stimulating mucin production by goblet cells, can effectively adhere to the inflamed colonic mucosa 17 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%